Update of Faecal Markers of Inflammation in Children with Cystic Fibrosis - Jung M. Lee; Steven T. Leach; Tamarah Katz; Andrew S. Day; Adam Jaffe; Chee Y. Ooi (Mediators of Inflammation)
There is evidence of intestinal inflammation in patients with CF. Intestinal inflammation may negatively impact the nutritional status of patient with CF, which adversely affects pulmonary function and survival. This paper provides an up-to-date review of intestinal inflammation in CF and an evaluation of utility of two specific faecal inflammatory markers (S100A12 and calprotectin).